The Implementation Of Satu Data Bencana Indonesia (SDBI) For Sustainable Development - Devid Marihot; Agus Wibowo; Sugeng Triutomo; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
The likelihood of disaster statistics is not the same across all countries and ups and downs over time. As country with the potential disasters more than 3.000 events every year, disaster data and statistics play an important role in reducing disaster risks and building resilience through estimating the risks, hazards and vulnerability. Therefore, the National Disaster Management Agency (BNPB) and the Central Statistical Agency (BPS) jointly developed Satu Data Bencana Indonesia (SDBI) as the official sectoral statistical domain within the National Statistical System to Disaster Statistical Framework (DRFS) established by UN ESCAP and was designed adhering to the principles of Satu Data Indonesia. Based on the background described above, research needs to be carried out as learning material to increase knowledge about intergovernmental-disaster data and its implementation for decision-makers. The method used is qualitative with a descriptive exploratory approach: data collection by observation, in-depth interviews, and documentation; data analysis techniques by data collection, data reduction, and data presentation. Several issues in implementing the platform of SDBI as regulated in the National Disaster Management Agency (BNPB) Regulations Number 1 of 2023 concerning Satu Data Bencana are weak coordination, non-standardized methodology, and poor communication. The conclusion from this study is that the methodological practices and procedures of disaster management for data collection and management should be shared with agencies involved in the technical working group to ensure coordination. The needs to form technical working group consisting of BPS, BNPB and BIG to minimize problems in implementing Satu Data Bencana Indonesia cannot be delayed to ensure the sustainability of nations ‘development.